ความคาดหวังของประชาชนต่อการดำเนินงานของโรงพยาบาลศูนย์สระบุรี - สุนีย์ เจริญกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this descriptive study was to investigate expectations of residents inside and outside the municipal area on Saraburi Regional Hospital’s operation in three dimensions : management, service and knowledge and their relationships with other factors, including sex, age, marital status, education, occupation, income, residence, received information, health service, distance from home to the hospital. The data of 378 people were collected by using a standardized questionnaires during 1 to 31 December 2000. The percentage, mean, Mann-Whitney บ test and Kruskal Wallis test were performed. The study found that the participant expected a medium level of Saraburi Regional Hospital s operation in overall and the three dimensions. However, the most people’s expectation was the service whereas the knowledge and the management were expected in the second and the third place respectively. The people outside the municipal area expected the Saraburi Regional Hospital’s operation greater than the people inside the municipal area in all the three dimensions. Furthermore, there were significant associations between the people’s expectations to Saraburi Regional Hospital’s operation and some of the factors, namely education, residence, distance from home to the hospital (p < 0.05). However, there were no association between people s expectations and the factors i.e. sex, age, marital status, occupation, income, received information and health service (p > 0.05). This study found that people expected the quality of the service more than their participation in the management and more hospital information is needed. Finally, the study recommends the improvement of the quality of the service in every sections and mobile clinic in community including the promotion in hospital s achievement.